Communication : making connections - Seiler, William J. 4 0 16; Beall, Melissa L.; 5 (Boston : Pearson/Allyn and Bacon, 2008)
An introduction to speech communication, focusing on the theme of connection and covering principles of public speaking, interpersonal and group communication, and other related topics, with a blend of theory, up-to-date research, and issues pertaining to daily life.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Communication.;Communication.; 20; 2